Peran Mahasiswa Kuliah Kerja Nyata dalam Pengembangan Ekonomi UMKM melalui Kegiatan Bazar di Desa Selayang - Lailan Syakira Taufan; Putri Ramadani; Putri Wahyuni; Ruth L. Sitakar; Rahmad Efendi (Pusat Riset dan Inovasi Nasional, 2026)
This study examines the role of KKN students in supporting the economic development of Micro, Small, and Medium Enterprises (MSMEs) through bazaar activities in Selayang Village. The bazaar programs facilitated by KKN students proved effective in improving product marketing, expanding business networks, increasing public awareness of local products, and ultimately raising the income of MSME actors. In addition to their economic impact, the bazaars functioned as promotional platforms and spaces for social interaction that strengthened relationships between community members and local entrepreneurs. Despite facing internal challenges such as limited funding, inadequate human resources, and a lack of product innovation, the initiative demonstrated positive outcomes. Collaboration among KKN students, local government, and the community is considered essential to ensure the sustainability of such empowerment programs. Overall, the findings indicate that bazaar activities represent an effective strategy for rural economic empowerment, contributing to the long-term competitiveness and growth of MSMEs while fostering community participation and local economic resilience.